Re-Strategising Mission (and Development) Intervention into Africa to Avoid Corruption, the Prosperity Gospel and Missionary Ignorance - Harries, Jim (Transformation, 2021)
The notion that Western ways are superior can be used to justify subsidising advocacy to the poor in Africa who might otherwise reject those ways out of ignorance. This ignores differences in culture that can trip up Western logic in Africa. When generosity is the reason to subsidise Western interventions, outside agents can be paid back in honour in ways not appropriate for Christians to accept. Perceived global inequalities used to convince donors to part with their money are impositions when those inequalities are not realised by recipients. When something inherently good, like the gospel, is routinely subsidised, some African people only value it when it comes with money. This disenfranchises poor evangelists. In order to overcome missionary ignorance, promotion of the prosperity gospel, and corruption associated with excessive foreign subsidies, this article advocates that vulnerable mission, namely, foreign intervention using local languages and resources, be permitted.